Molten Salts and Pyrochemical Processing Progress at the UK’s National Nuclear Laboratory - Carvajal-Ortiz Ruth; Edmondson Mike J.; Hay Moya (EPJ Web of Conferences)
The UK’s National Nuclear Laboratory offers infrastructure and capabilities to support research and development programmes for advanced fuel cycles and partitioning and transmutation (P&T). Our world-leading facilities have been widely used as part the UK government funded Advance Fuel Cycle Programme. Part of the programme involved the development of molten salt and pyrochemical processing capabilities including fuel manufacture, salt science, engineering, online monitoring, and fuel cycle integration. This has led to a resurgence of activity in molten salt technologies for nuclear application.